2007
DOI: 10.1523/jneurosci.1940-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Linking Neuronal and Behavioral Performance in a Reaction-Time Visual Detection Task

Abstract: Perceptual decisions are likely to be based on signals that are provided by populations of neurons in early sensory cortical areas. How these neural responses are combined across neurons and over time to mediate behavior is unknown. To study the link between neural responses and perceptual decisions, we recorded the activity of single units (SU) and multiple units (MU) in the primary visual cortex (V1) of monkeys while they performed a reaction-time visual detection task. We then determined how well the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 48 publications
13
93
3
Order By: Relevance
“…Using spike count measurements, previous studies have reported significant choice-related activities in many cortical areas during a variety of behavioral tasks (Bosking and Maunsell 2011;Britten et al 1996;Cook and Maunsell 2002;Dodd et al 2001;Grunewald et al 2002;Liu and Newsome 2005;Nienborg and Cumming 2006;Palmer et al 2007;Parker et al 2002;Price and Born 2010;Purushothaman and Bradley 2005;Uka and DeAngelis 2004;Uka et al 2005). Similarly, our previous study reported above chance choice probabilities for both P and M LGN neurons (Jiang et al 2015b).…”
Section: Choice-related Activitysupporting
confidence: 66%
See 1 more Smart Citation
“…Using spike count measurements, previous studies have reported significant choice-related activities in many cortical areas during a variety of behavioral tasks (Bosking and Maunsell 2011;Britten et al 1996;Cook and Maunsell 2002;Dodd et al 2001;Grunewald et al 2002;Liu and Newsome 2005;Nienborg and Cumming 2006;Palmer et al 2007;Parker et al 2002;Price and Born 2010;Purushothaman and Bradley 2005;Uka and DeAngelis 2004;Uka et al 2005). Similarly, our previous study reported above chance choice probabilities for both P and M LGN neurons (Jiang et al 2015b).…”
Section: Choice-related Activitysupporting
confidence: 66%
“…Basic procedures in computing choice probabilities were similar to those described in previous studies Jiang et al 2015a,b;Palmer et al 2007). When using spike count distributions, the proportions of choice-inside-receptive-field trials (i.e., trials in which the monkey made a saccade towards the receptive field location) were plotted against the proportions of choice-outside-receptive-field trials that exceeded all the possible spike count criteria (in number of spikes), and the area under the ROC curve was taken as the choice probability value for that contrast level.…”
Section: Discussionmentioning
confidence: 99%
“…after the analyses of Britten et al (1992) and Palmer et al (2007), where x is sound pressure level, and 位 and k represent the threshold and slope parameter. However, since the monkeys' false alarm rates influenced both the maximum performance and the estimate of chance performance at sound levels below threshold, these probabilities were allowed to be free parameters in our fitting method.…”
Section: Discussionmentioning
confidence: 99%
“…One method that has been widely used to suggest that signals from particular neurons contribute to a given perceptual decision combines threshold psychophysics with single-unit recordings. A trialto-trial correlation between neuronal activity and perceptual judgment, which cannot be explained by the visual stimulus, is taken as evidence that neuronal signals contribute to a decision [1][2][3][4][5][6][7] . Such correlation, often quantified by 'choice probability', should then also depend on the task strategy employed by the subject 6 .…”
Section: Introductionmentioning
confidence: 99%